Functionalized sodium alginate composite films based on double-encapsulated essential oil of wampee nanoparticles: a green preservation material - Jinman He; Wanli Zhang; Gulden Goksen; Mohammad Rizwan Khan; Naushad Ahmad; Xinli Cong (Food Chemistry: X)
In this study, zein-pectin nanoparticles loaded with Wampee [Clausena lansium (Lour.) Skeels] (WEO) were developed. The particle size of the nanoparticles is 515.9 nm, polydispersity index is 0.4 and zeta potential is −39.3 mV. Subsequently, the ZWP was incorporated into sodium alginate (SA)-based film (ZWP-S). The films were then analyzed to determine their physical properties and thermal stability, and also to examine their microstructure and intermolecular forces using SEM, FTIR, and XRD techniques. Additionally, the films were evaluated for their antimicrobial and antioxidant activity, as well as their ability to sustain the release of WEO. Overall, the ZWP-S film conferred excellent functional properties, including UV barrier performance, mechanical properties (21 % increase in tensile strength), water sensitivity, stability, more compact structure, high antioxidant activity and long-lasting antimicrobial activity, surpassing those of the control film. Consequently, it was applied as a novel coating for preserving strawberries, rotting rate of strawberries was reduced by 43 % at 6d, yielding promising results in prolonging the freshness of the fruit.